Strategi Membangun Kemampuan Logis Matematis Bagi Siswa Sekolah Dasar - Sugilar, Hamdan (Journal of Contemporary Issue in Elementary Education, 2023)
Mathematical logical abilities are really needed, one of which is in solving complex problems that students will face, for this reason they need to be trained, studied and conveyed to students. This research method is qualitative descriptive research with a literature study approach from various book sources, journal articles and other relevant sources. The research results showed that mathematical logical abilities can be trained through methods, media, and mathematical problems in the form of questions in the form of educational games, computational thinking (CT) questions, and puzzles because they are related to students' ability to solve problems by drawing conclusions through logical reasoning. The practical benefits of students studying CT are improving problem solving abilities, improving logical thinking and analytical abilities. The advantage of students learning educational games, puzzles and HOTS questions is that they train and develop students' abilities to think logically, critically and creatively.